Asymptotic Behavior of the Coupled Nonlinear Schrödinger Lattice System - Hengyan Li; Xin Zhao (Abstract and Applied Analysis, 2014)
This paper studies asymptotic behavior of solutions for the coupled nonlinear Schrödinger lattice system. We obtain the existence and stability of compact attractor by means of tail estimates method and finite-dimensional approximations.